2021
DOI: 10.18632/aging.203232
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic mebendazole (MBZ) effectively overcomes cisplatin resistance in human ovarian cancer cells by inhibiting multiple cancer-associated signaling pathways

Abstract: Ovarian cancer is the third most common cancer and the second most common cause of gynecologic cancer death in women. Its routine clinical management includes surgical resection and systemic therapy with chemotherapeutics. While the first-line systemic therapy requires the combined use of platinum-based agents and paclitaxel, many ovarian cancer patients have recurrence and eventually succumb to chemoresistance. Thus, it is imperative to develop new strategies to overcome recurrence and chemoresistance of ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…Moreover, this might have important clinical implications as it implies that one could use mebendazole together with cisplatin as combination regimen to substitute for cisplatin and doxorubicin treatments [ 8 ] in order to reduce toxic side effects of doxorubicin. In line with our results, a first study has recently demonstrated that mebendazole could overcome cisplatin resistance in ovarian cancer in vitro [ 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this might have important clinical implications as it implies that one could use mebendazole together with cisplatin as combination regimen to substitute for cisplatin and doxorubicin treatments [ 8 ] in order to reduce toxic side effects of doxorubicin. In line with our results, a first study has recently demonstrated that mebendazole could overcome cisplatin resistance in ovarian cancer in vitro [ 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…All recombinant adenoviruses were constructed by using the AdEasy technology 24 . The Ad‐FLuc, which co‐expresses firefly luciferase (FLuc) and GFP, was generated as described in our previous studies 25–27 . For the construction of Ad‐IL10, the coding region of human IL‐10 was PCR amplified and subcloned into an adenoviral shuttle vector, pAdTrack‐CMV.…”
Section: Methodsmentioning
confidence: 99%
“… 24 The Ad‐FLuc, which co‐expresses firefly luciferase (FLuc) and GFP, was generated as described in our previous studies. 25 , 26 , 27 For the construction of Ad‐IL10, the coding region of human IL‐10 was PCR amplified and subcloned into an adenoviral shuttle vector, pAdTrack‐CMV. The resultant vector was used to generate the recombinant adenoviral plasmid pAd‐IL10 through homologous recombination with an adenoviral backbone vector in bacterial BJ5183 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Mebendazole (MBZ) is a multi-purpose anti-parasitic drug that reduces cisplatin resistance in OC and inhibit tumour proliferation, wound healing, cell migration and apoptosis by activating multiple signalling pathways. They consist of a member of the Ets (E twenty-six) oncogene family of transcription factors/dimer of serum response factor (ELK/SRF), Nuclear factor kappa beta – myelocytomatosis - viral oncogene homolog (NF-kB/MYC/MAX), and E2F/DP1) associated with human ovarian cancer [ 161 ]. Oleuropein, a phenolic ingredient, upregulated the expression of p21, p53, TNF Receptor Superfamily Member 10b (TNFRSF10B), miR-34a, miR-125b and miR-16 with the suppression of Bcl-2 and myeloid cell leukemia protein-1 (Mcl-1).…”
Section: Recent Advances In Cisplatin-associated Ovarian Cancermentioning
confidence: 99%